Assessment of natural radionuclides mobility in a phosphogypsum disposal area. (November 2018) - Pérez-Moreno, S.M.; Gázquez, M.J.; Pérez-López, R.; Vioque, I.; Bolívar, J.P.
Abstract: The phosphogypsum (PG) stacks located at Huelva (SW Spain) store about 100 Mt of PG, and covers a surface of 1000 ha. It has been very well established in many studies that this waste contains significant U-series radionuclides concentrations, with average activity concentrations rounding the 650, 600, 400 and 100 Bq kg −1 for 226 Ra, 210 Po, 230 Th and 238 U, respectively. However, the radionuclide transfer from this repository into the environment by the aquatic pathway will depend on the mobility of each radionuclide. The mobility of the natural radionuclides (U-isotopes, Th-isotopes, 226Ra, and 210Po) contained in the PG piles were evaluated by using the optimized BCR sequential extraction procedure (BCR "Community Bureau of Reference"). The radionuclides were measured in the liquid fractions by alpha-particle spectrometry with semiconductor PIPS detectors. In addition, to validate the obtained results, waters from different locations of the PG piles (pore-water, perimeter channel and edge outflow leachates) were taken and the alpha emitter radionuclides determined. Uranium presents the highest mobility, being its total mobile fraction in the PG around 70%, while 210Po and 226Ra present an intermediate mobility of (around 50% and 30%, respectively). And finally, the Th-isotopes have very low mobility (mobile fraction < 5%), being fixed to the residual fraction. It is noteworthy that this behaviour has been also found in the water samples taken from the stacks, demonstrating that this sequential leaching operational methodology is a useful tool for assessing the release capacity of radionuclides by inorganic wastes. Highlights: Natural radionuclides mobility in phosphogypsum (PG) coming from Morocco sedimentary ore by using the optimized BCR sequential extraction procedure was studied. Uranium is the radioelement that presents the highest mobility (around 70%), while the Th-isotopes are very bound to the PG (mobile fraction < 5%). 210 Po and 226 Ra present an intermediate mobility (around 50% and 30%, respectively). BCR results were validated by using the natural radionuclides levels in waters from PG piles.